Epitranscriptomics: RNA Modifications in Bacteria and Archaea - Höfer, Katharina; Jäschke, Andres (Microbiology spectrum, 2018)
The increasingly complex functionality of RNA is contrasted by its simple chemical composition. RNA is generally built from only four different nucleotides (adenine, guanine, cytosine, and uracil). To date, >160 chemical modifications are known to decorate RNA molecules and thereby alter their function or stability. Many RNA modifications are conserved throughout bacteria, archaea, and eukaryotes, while some are unique to each branch of life. Most known modifications occur at internal positions, while there is limited diversity at the termini. The dynamic nature of RNA modifications and newly discovered regulatory functions of some of these RNA modifications gave birth to a new field, now often referred to as “epitranscriptomics.” This review highlights the major developments in this field and summarizes detection principles for internal as well as 5′-terminal mRNA modifications in prokaryotes and archaea to investigate their biological significance.
Gesehen am 04.03.2020